Risk factors for uterine fibroids: reduced risk associated with oral contraceptives. Issue 6543 (9th August 1986) - Ross, R K; Pike, M C; Vessey, M P; Bull, D; Yeates, D; Casagrande, J T
Abstract : Risk factors for pathologically confirmed uterine leiomyomas (fibroids) were investigated using data from the Oxford Family Planning Association study, a long term follow up study of women using various methods of contraception. For each of 535 women who had had a fibroid an individual control was selected who matched the patient on age, date of entry into the cohort, and family planning clinic at recruitment and who was alive (and still being followed up) at the date the patient underwent surgery for fibroids. Case-control analysis showed that reproductive experiences were closely linked to development of fibroids. Risk of fibroids decreased consistently with increasing number of term pregnancies; women with five term pregnancies had only a quarter of the risk of women who had had none. Risk also decreased consistently with increasing duration of oral contraceptive use; the risk of fibroids was reduced by some 31% in women who had used oral contraceptives for 10 years. Risk was strongly related to weight: women who weighed under 55 kg had a particularly low risk, and overall the risk rose roughly 21% for each 10 kg increase. Cigarette smoking was associated with a decreased risk of fibroids; smokers of 20 cigarettes a day had a risk roughly two thirds that of non-smokers. These risk factors have all previously been identified as risk factors for endometrial cancer; this strongly suggests that the underlying risk factor is "unopposed" oestrogen.